เพลงเดี่ยวนกขมิ้นสามชั้น ทางฆ้องมอญ 6 ลูก ทางครูสมชาย ดุริยประณีต กรณีศึกษาครูธีระศักดิ์ ชุ่มชูศาสตร์ - บุญธรรม, อนุพันธ์ (Academic Journal Phranakhon Rajabhat University, 2017)
The purposes of this research were to study: 1)To study the biography ,structure, key-scale, melodic pattern of PlengDeawNokKaminSamchanTarng Kong Mon Hok Look. 2)To analysis PlengDeawNokKaminSamchanTarng Kong Mon Hok Look of KruSomchai Duriyapraneet. 3) To study the role of PlengDeawNokKaminSamchan in Thai culture. This research methodology using the qualitative research. Population (Keylnformants) was 10 people. There search instruments were collected by interviews, observations and collect data from various recording. The data were analyzed by content analysis. The results were as follows: 1)The biography, structure, key-scale, melodic pattern of PlengDeawNokKaminSamchanTarng Thai and Tarng Kong Mon. PlengDeawNokKaminTarng Kong Mon Hok Look of KruSomchai Duriyapraneet can be used as evidence in music education other side. 2)The unique style of PlengDeawNokKaminSamchanTarng Kong Mon Hok Look of KruSomchai Duriyapraneet applied to the study of PlengDeaw Kong Mon and other songs. 3) This academic paper is a guide to those who want to research about the role of PlengDeawNoKKaminSamchanTarng Kon Mon Hok Look of KruSomchaiDuriyapraneet.